(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
As a result of the informatization of the society, new researches are emerging in the world of media and related to it in our linguistics, in particular, certain scientific views about media texts that take a wider border compared to the text. Studying in world linguistics the types and characteristics of media texts created because of the interaction of linguistic and visual components, as well as the different aspects of media texts used in the press, radio, television and Internet networks will be passed.